1990
DOI: 10.1152/jappl.1990.68.4.1475
|View full text |Cite
|
Sign up to set email alerts
|

Adjustments in oxygen transport during head-out immersion in water at different temperatures

Abstract: Respiratory gas exchange was investigated in human subjects immersed up to the shoulders in water at different temperatures (Tw = 25, 34, and 40 degrees C). Cardiac output (Qc) and pulmonary tissue volume (Vti) were measured by a rebreathing technique with the inert gas Freon 22, and O2 consumption (VO2) was determined by the closed-circuit technique. Arterial blood gases (PaO2, PaCO2) were analyzed by a micromethod, and alveolar gas (PAO2) was analyzed during quiet breathing with a mass spectrometer. The find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…The hydrostatic counter-pressure occurring with water immersion causes an increase in . Q, central blood volume, and pulmonary arterial pressure (Choukroun & Marene, 1990). Central hypervolemia occurring with water immersion results in a delayed .…”
Section: Role Of the Diving Responsementioning
confidence: 99%
“…The hydrostatic counter-pressure occurring with water immersion causes an increase in . Q, central blood volume, and pulmonary arterial pressure (Choukroun & Marene, 1990). Central hypervolemia occurring with water immersion results in a delayed .…”
Section: Role Of the Diving Responsementioning
confidence: 99%
“…Water immersion has been shown to induce several cardiopulmonary changes, including increases in c and stroke volume (Choukroun and Varene 1990;Farhi and Linnarsson 1977;Rowell 1993). On the other hand, it has been suggested that the oxygen transport response by the circulation alters the O 2 response (Hughson 1984;Hughson et al 1991).…”
Section: Eect Of the Increases In C And Oxygen Stores On O 2 Responsementioning
confidence: 99%
“…Craig and Dvorak (1968) showed that the water temperature required for thermoneutrality was lower during dynamic exercises than at rest. Water temperature of between 29 C and 33 C is thought to be thermoneutral during dynamic exercises (Choukroun and Varene, 1990;Israel et al, 1989;Choukroun and Varene, 1989;McArdle et al, 1976). WI below thermoneutral water temperature causes peripheral vasoconstriction resulting in an increase of the central blood volume (McArdle et al, 1976), which then leads to a decrease of HR and an increase of stroke volume (SV).…”
Section: Introductionmentioning
confidence: 99%